Macronutrients deficiency in Heliconia psittacorum x Heliconia spathocircinata ‘Golden Torch’ - Castro, Ana Cecília; Willadino, Lilia; Loges, Vivian; Castro, Mario Felipe; Aragão, Fernando Antônio (Revista Ciência Agronômica, 2015)
The objective of this study was to characterize nutritional deficiencies in Heliconia psittacorum x Heliconia spathocircinata ‘Golden Torch’, through growth indicators, symptomatology and macronutrients contents in leaves and underground plant part. The experiment was carried out in a greenhouse, with eight treatments comprising complete nutrition solution (N, P, K, Ca, Mg, S), solution with individual nutrient omission of N, P, K, Ca, Mg or S and solution lacking all nutrients. The symptoms of nutrients deficiency appeared in the following occurrence order: N, K, P, Mg and S. Deficiency symptoms were: general chlorosis to - N omission; slight chlorosis to - P and - S; dark green leaves and necrosis to - K; marginal chlorosis and necrosis to - Mg. Calcium omission did not cause any visual symptom. Deficiencies in N and P affected more intensely shoot number, leaf dry mass production, total leaf number and leaf area. Among the evaluated leaves, there was a tendency of a highest decrease in the contents in the third leaf.